2021
DOI: 10.1007/s10664-021-09999-9
|View full text |Cite
|
Sign up to set email alerts
|

Industry practices and challenges for the evolvability assurance of microservices

Abstract: Context Microservices as a lightweight and decentralized architectural style with fine-grained services promise several beneficial characteristics for sustainable long-term software evolution. Success stories from early adopters like Netflix, Amazon, or Spotify have demonstrated that it is possible to achieve a high degree of flexibility and evolvability with these systems. However, the described advantageous characteristics offer no concrete guidance and little is known about evolvability assu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 31 publications
(42 reference statements)
0
23
0
Order By: Relevance
“…A large set of challenges was identified by practitioners in a large study on microservice evolvability [1]. Missing system-centric perspectives, inter-service dependencies, coordination between decentralized teams, and challenges with outdated documentation, were the most frequently mentioned issues.…”
Section: Discussion On Implicationsmentioning
confidence: 99%
“…A large set of challenges was identified by practitioners in a large study on microservice evolvability [1]. Missing system-centric perspectives, inter-service dependencies, coordination between decentralized teams, and challenges with outdated documentation, were the most frequently mentioned issues.…”
Section: Discussion On Implicationsmentioning
confidence: 99%
“…That requires engineers to understand what happened across the entire service graph at the time of the debugging, which seems to counter to the ethos of microservices architectures in the first place. Bogner et al focused on this challenge in a systematic grey literature review [3]. They concluded that most painful challenges in the microservices industry are the Service-cutting and No-System-Centric views.…”
Section: Problem and Motivationmentioning
confidence: 99%
“…Microservice development comes from practitioners, and research tends to come later, so publications about microservices are still limited in a lot of areas. Thus, grey literature may hold valuable insights that academic literature simply cannot provide yet [52].…”
Section: E Microservice Visualization In the Industrymentioning
confidence: 99%